Analysis of Junior High School Students Misconceptions About the Human Excretion Using a Four-Tier Diagnostic Test - Saputri*, Irma Dwi; Rusyati, Lilit (Jurnal IPA & Pembelajaran IPA, 2024)
This study aimed to measure middle school students conceptions and misconceptions related to human excretion using a four-tiered diagnostic test. Using a cross-sectional survey design, responses of 113 eighth-grade students, convenience sampled from two schools in Bandung were collected. A four-tiered instrument was developed specifically for the focus of this study and the data analyzed below consists of test results and interviews with teachers. The findings indicate that students conceptions of the human excretory system fall into several categories: scientific knowledge (SK) at 46.90%, false positive (FP) at 13.09%, false negative (FN) at 6.13%, misconception (M) at 20.45%, and lack of knowledge (LK) at 13.43%. The most common misconceptions relate to diseases and disorders (38%) and sweating and body thermoregulation (31%). These misconceptions may arise due to factors such as students lack of enthusiasm for learning and limited engagement during the learning process. Consequently, there is a need for improved teaching approaches to address misconceptions associated with human excretion and to foster a more comprehensive scientific understandingamongstudents.